ODS. las voces de la universidad y la empresa - (:unkn) unknown (Kolima (Madrid, España))
El 25 de septiembre del 2015, la Asamblea General de la ONU adoptó la Agenda 2030 para el Desarrollo Sostenible, un plan de acción a favor de las personas, el planeta y la prosperidad. La Agenda planteó 17 Objetivos con 169 metas de carácter integrado e indivisible que abarcaban las esferas económica, social y ambiental, y que regiría los programas de desarrollo mundiales durante los próximos quince años. Siete años después, y tras el parón imprevisto y devastador que ha supuesto la pandemia del Covid-19 en muchos sentidos, este libro ofrece un magnífico crisol de reflexiones de investigadores, profesores universitarios, empresarios y otros profesionales que, cada uno desde su perspectiva, analizan los retos y oportunidades actuales de este gran proyecto de transformación global. Es nuestro deber emerger de la reciente crisis acelerando el avance hacia la consecución de los ODS. Las experiencias del último año y medio, a menudo adquiridas con gran dolor, pero también dotadas de un enorme calado, deben llevarnos a repensar nuestro modo de actuar, pues no debemos olvidar que la Agenda 2030 implica, ante todo, un cambio radical en los modelos socioeconómicos previos a la irrupción del Covid-19. Pero, como se menciona en este libro, no se trata únicamente de intentar hacer las cosas bien, sino de hacerlas «conscientemente bien», es decir, enfocando nuestras acciones hacia el cumplimiento de los objetivos marcados. Y, para poder contribuir a esta gran tarea colectiva, los objetivos de cada agente, ya sean individuos, empresas o administraciones, deben ser lo suficientemente ambiciosos, pero a la vez reales y concretos. El lector descubrirá en los artículos que componen esta obra nuevas ideas para la acción coordinada de individuos, empresas y Administraciones para el impulso de la Agenda 2030 y, con ella, de una nueva forma de progreso más ética y sostenible en beneficio del conjunto de la sociedad.

On September 25, 2015, the UN General Assembly adopted the 2030 Agenda for Sustainable Development. the 2030 Agenda for Sustainable Development, an action plan for people, planet and prosperity. people, planet and prosperity. The Agenda set out 17 Goals with 169 integrated and indivisible targets covering economic, social and environmental economic, social and environmental spheres, which would govern the world's development programs over the next 15 years. development programs over the next fifteen years. Seven years later, and after the unforeseen and devastating hiatus brought about by the Covid-19 pandemic the Covid-19 pandemic in many respects, this book offers a magnificent melting pot of reflections of reflections from researchers, university professors, business people and other professionals who, each in his or her own and other professionals who, each from his or her own perspective, analyze the current challenges and opportunities for the the current challenges and opportunities of this great project of global transformation. global transformation. It is our duty to emerge from the recent crisis by accelerating progress towards the SDGs. the achievement of the SDGs. The experiences of the past year and a half, often often with great pain, but also with great significance, must lead us to rethink the must lead us to rethink our way of acting, for we must not forget that the 2030 Agenda that the 2030 Agenda implies, first and foremost, a radical change in the socio-economic models that preceded in the socioeconomic models that existed prior to the emergence of Covid-19. But, as mentioned in this book, it is not only a matter of trying to do things right, but also of doing things right. to do things well, but to do them "consciously well", i.e., by focusing our actions on the that is, focusing our actions on achieving the objectives we have set ourselves. And, in order to contribute to this great collective task, the objectives of each agent, whether individuals of each agent, whether individuals, companies or administrations, must be sufficiently ambitious, yet be sufficiently ambitious, but at the same time real and concrete. The reader will discover in the articles that make up this book new ideas for the coordinated action of individuals, companies and administrations. for the coordinated action of individuals, companies and administrations to promote the 2030 Agenda to promote the 2030 Agenda and, with it, a new form of progress that is more ethical and sustainable for the benefit of the planet. and sustainable progress for the benefit of society as a whole. On September 25, 2015, the UN General Assembly adopted the 2030 Agenda for Sustainable Development. the 2030 Agenda for Sustainable Development, an action plan for people, planet and prosperity. people, planet and prosperity. The Agenda set out 17 Goals with 169 integrated and indivisible targets covering economic, social and environmental economic, social and environmental spheres, which would govern the world's development programs over the next 15 years. development programs over the next fifteen years. Seven years later, and after the unforeseen and devastating hiatus brought about by the Covid-19 pandemic the Covid-19 pandemic in many respects, this book offers a magnificent melting pot of reflections of reflections from researchers, university professors, business people and other professionals who, each in his or her own and other professionals who, each from his or her own perspective, analyze the current challenges and opportunities for the the current challenges and opportunities of this great project of global transformation. global transformation. It is our duty to emerge from the recent crisis by accelerating progress towards the SDGs. the achievement of the SDGs. The experiences of the past year and a half, often often with great pain, but also with great significance, must lead us to rethink the must lead us to rethink our way of acting, for we must not forget that the 2030 Agenda that the 2030 Agenda implies, first and foremost, a radical change in the socio-economic models that preceded in the socioeconomic models that existed prior to the emergence of Covid-19. But, as mentioned in this book, it is not only a matter of trying to do things right, but also of doing things right. to do things well, but to do them "consciously well", i.e., by focusing our actions on the that is, focusing our actions on achieving the objectives we have set ourselves. And, in order to contribute to this great collective task, the objectives of each agent, whether individuals of each agent, whether individuals, companies or administrations, must be sufficiently ambitious, yet be sufficiently ambitious, but at the same time real and concrete. The reader will discover in the articles that make up this book new ideas for the coordinated action of individuals, companies and administrations. for the coordinated action of individuals, companies and administrations to promote the 2030 Agenda to promote the 2030 Agenda and, with it, a new form of progress that is more ethical and sustainable for the benefit of the planet. and sustainable progress for the benefit of society as a whole.
Libro de Investigación
Keywords: Cátedra Iberdrola de Ética Económica y Empresarial